PERILAKU YAKI (Macaca nigra) DI KANDANG HABITUASI GUNUNG MASARANG - Alfa Jevian Pariama; Martina A. Langi; Johny S. Tasirin (Universitas Sam Ratulangi, 2022)
Abstract The aims to study the daily behavior of Macaca nigra in habituation cage on Mount Masarang, Tomohon city. Data collection was carried out for 2 (two) weeks, from November to December 2022. Daily behavior recording used instantaneous sampling, namely recording behavior at intervals of one minute, the methods used were observation and focal animal sampling. The result showed that the highest proportion of daily behavior of Macaca nigra in the Habituation Cage of Mount Masarang, Tomohon City is social behavior 36.6% followed by moving behavior 27.6% and feeding 24.5% the rest is used for resting 11.3%. The frequency of activity of Macaca nigra male is higher than Macaca nigra female, namely 169 times a day while Macaca nigra female 149 times a day. Keywords: Behavior, Macaca nigra, habituation cage, Masarang Pendahuluan Pulau Sulawesi mempunyai